Structural performance of a parked wind turbine tower subjected to strong ground motions. (1st August 2016) - Patil, Atul; Jung, Sungmoon; Kwon, Oh-Sung
Highlights: We evaluate the seismic performance of a typical wind turbine tower. Both near-fault and far-fault ground motions were used for comprehensive study. Fragility functions were obtained considering uncertainties in capacity and demand. The wind turbine tower studied here is most vulnerable to the overturning. Abstract: The objective of this paper is to evaluate the structural performance of a typical wind turbine tower subjected to strong ground motions. A detailed finite element model of an 80 m wind turbine tower was developed and subjected to strong ground motions. Two sets of input ground motions were used: one with pulse-type near-fault motions and the other one with far-fault motions. The structural performance of the wind turbine tower was investigated through seismic fragility analysis. The potential limit states were defined as global buckling of the tower, first occurrence of yielding, overturning of the foundation and permanent deformation of the tower. It was found that the wind turbine tower investigated in this study is most vulnerable to the overturning in the event of an earthquake. Yielding of the tower is the second most probable failure mechanism, which is followed by development of permanent deformation and global buckling of the tower. Similar trends in the failure mechanism were observed for both near-fault and far-fault ground motions.